2018
DOI: 10.1177/2046147x18764216
|View full text |Cite
|
Sign up to set email alerts
|

Who loves consent? Social media and the culture jamming of Victoria’s Secret

Abstract: This study explores responses to the culture jamming of Victoria’s Secret’s by a feminist activist organization called FORCE. Using social media, FORCE was able to troll Victoria’s Secret by masking themselves as part of the brand and community through the campaign Pink Loves Consent. This act of dissensus disguised as consensus created an entry point into conversation with followers of Victoria’s Secret, spurring an online dialogue about creating a consent-based culture. This study provides recommendations fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Relevant research investigates how parody and irony are used as creative and disruptive tools in order to articulate social protest against established communication orders. Culture jamming may be agonistic when creating ‘productive dissensus’ (Madden et al, 2018: 183), but appropriation as its key strategy also has a downside (Heath and Potter, 2006). This study showed how the provocative social protest against Nike’s campaign ultimately turned into an affirmative replication of Nike’s own communicative framework.…”
Section: Resultsmentioning
confidence: 99%
“…Relevant research investigates how parody and irony are used as creative and disruptive tools in order to articulate social protest against established communication orders. Culture jamming may be agonistic when creating ‘productive dissensus’ (Madden et al, 2018: 183), but appropriation as its key strategy also has a downside (Heath and Potter, 2006). This study showed how the provocative social protest against Nike’s campaign ultimately turned into an affirmative replication of Nike’s own communicative framework.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, the strategy of trapping shows how platform features such as hashtags, flagging and reporting and generating fake accounts are used to oppose the political actorhood of the brand. Some of these resistance strategies borrow from cultural jamming by altering and parodying the original message (Carducci, 2006; Klein, 1999; Harold, 2004; Madden et al , 2018; Thompson et al , 2006). These practices also reflect the varying nature of networked publics and online consumer cultures on different platforms (Arvidsson and Caliandro, 2016; Van Dijck, 2013); the most hostile voices were found on anonymous online forums, where subcultures appropriated the campaign language and hashtags for their own purposes and the campaign gained an afterlife.…”
Section: Discussionmentioning
confidence: 99%
“…Embodied direct action is a crucial part of driving attention to PETA's other channels and messages. And, as Madden, Janoske, Winkler, and Harpole (2018) pointed out, social media use intersects with these other activist strategies, providing the "opportunity and support for continuing to develop and galvanize that group repeatedly over time" (p. 182). This study thus points to the need to explore the interplay between the visual nature of direct action and its online circulation.…”
Section: Implications and Conclusionmentioning
confidence: 99%